Combination therapy of three-dimensional (3D) visualisation operative treatment planning system and US-guided percutaneous microwave ablation in larger renal cell carcinomas (D ≥ 4 cm): preliminary results. (3rd April 2017) - Li, Xin; Yu, Jie; Liang, Ping; Yu, Xiaoling; Cheng, Zhigang; Han, Zhiyu; Huang, Hui; Duan, Shaobo; Zheng, Jiasheng
Abstract: Purpose: To analyse the clinical outcomes of combination therapy of three-dimensional (3D) visualisation operative treatment planning system and US-guided percutaneous microwave ablation (PMWA) in larger renal cell carcinomas (RCCs) (D ≥ 4 cm). Materials and methods: The results from 20 patients with 20 larger RCCs treated with a 3D visualisation operative treatment planning system and US-guided PMWA were reviewed retrospectively. The patients were followed up by contrast-enhanced images at 1, 3, and 6 months and every 6 months thereafter. The outcomes of overall survival and local tumour progression rate were statistically analysed. Results: The median follow-up period was 26 months. The mean time of ablation for one tumour was 1.1 ± 0.3 sessions. The average number of ablation points of one tumour was 4.5 ± 0.9. The mean output power of ablation was 50.50 ± 2.2 W. The mean time of ablation for one tumour was 1374.4 ± 391.1 s. Artificial ascites was used in 12 (60%) tumours adjacent to the intestinal tract, and thermal monitoring system was used in all tumours (100%). Technical effectiveness and metastasis-free status were achieved in all tumours. The 1- and 2-year local tumour progression rates were both 5%. The cancer-specific survival rate and 2-year overall survival rates were both 100%. No severe major complications occurred. There was no significant difference in creatinine or urea nitrogen before or 3 days after ablation. Conclusions: Combination therapy of 3D visualisation operative treatment planning system and US-guided PMWA appeared to be a safe and effective technique for the management of larger RCCs, which could improve clinical efficacy.